Thailand's Health Workforce : A Review of Challenges and Experiences - Pagaiya, Nonglak (World Bank, Washington, DC, 2013)
Thailand's health system is a dynamic entity that continues to change and grow. The country's health policies greatly affect the health workforce, the choices they make, their numbers and their availability. This paper explores the relationship between Thai health workers and the policies that affect them.